FEATURES OF THE LEGAL STATUS TRANSPORT ENTERPRISES - Рябова, Катерина Олексіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article is devoted to the analysis of the legal status of transport enterprises and the relation between such categorical notions as «subjects of transport legal relations» and «transport enterprises». Methods: the approaches of different scientists concerning the definition of «subjects of transport legal relations» are analyzed. Results: the author focuses on the meaning of the concept of «transport enterprises» throughout the prism of the subjective structure of transport relations. Discussion: problems of the domestic legislation and filling the vacuum of legal regulation of the legal status of transport enterprises.